Pyrene Functionalized Highly Reduced Graphene Oxide-palladium Nanocomposite: A Novel Catalyst for the Mizoroki-Heck Reaction in Water - Khan, Mujeeb; Ashraf, Muhammad; Shaik, Mohammed Rafi; Adil, Syed Farooq; Islam, Mohammad Shahidul; Kuniyil, Mufsir; Khan, Merajuddin; Hatshan, Mohammad Rafe; Alshammari, Riyadh H.; Siddiqui, Mohammed Rafiq H.; Tahir, Muhammad Nawaz (Frontiers in Chemistry, 2022)
The formation of C-C bond through Mizoroki-Heck cross-coupling reactions in water with efficient heterogeneous catalysts is a challenging task. In this current study, highly reduced graphene oxide (HRG) immobilized palladium (Pd) nanoparticles based catalyst (HRG-Py-Pd) is used to catalyze Mizoroki-Heck cross coupling-reactions in water. During the preparation of catalyst, amino pyrene is used as smart functionalizing ligand, which offered chemically specific binding sites for the effective and homogeneous nucleation of Pd NPs on the surface of HRG, which significantly enhanced the physical stability and dispersibility of resulting catalyst in aqueous medium. Microscopic analysis of the catalyst revealed the uniform distribution of ultrafine Pd NPs on solid support. The catalytic properties of HRG-Py-Pd is tested towards the Mizoroki-Heck cross-coupling reactions of various aryl halides with acrylic acid in aqueous medium. Furthermore, the catalytic efficacy of HRG-Py-Pd is also compared with its non-functionalized counterpart such as HRG-Pd and pristine Pd NPs. Using the HRG-Py-Pd nanocatalyst, a highest conversion of 99% is achieved in the coupling reaction of 4-bromoanisol and acrylic acid in aqueous solution in a relatively short period of time (3 h), with less quantity of catalyst (3 mg). Comparatively, pristine Pd NPs has delivered lower conversion ( 92%) for the same reaction, but required long reaction time and large amount of catalyst (5.3 mg), whereas, the HRG-Pd has not delivered any conversion.